2016
DOI: 10.1186/s12917-016-0916-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and genetic characterization of Cryptosporidium species and Giardia duodenalis in lambs in Oromia Special Zone, Central Ethiopia

Abstract: Background Cryptosporidium and Giardia duodenalis are gastro-intestinal parasites that infect human and animals worldwide. Both parasites share a broad host range and are believed to be zoonosis. The aim of this study was to identify the species of Cryptosporidium and assemblages of G. duodenalis in lambs and to elucidate their role in zoonotic transmission.ResultsA total of 389 fecal samples were collected from lambs and screened by microscopy and nested PCR targeting the small-subunit ribosomal RNA for Crypt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
3
15
3
Order By: Relevance
“…Among developing countries, a small number of C. parvum infections have been reported in goats and sheep from Asia, including China [ 17 , 47 , 48 ], India [ 49 ], Jordan [ 50 ] and Turkey [ 51 ]. Our results, however, are in contrast to those from studies conducted in most African countries including Egypt [ 37 ], Tunisia [ 52 ] and Ethiopia [ 53 ], where C. parvum has thus far not been reported in small ruminants. Cryptosporidium parvum was also absent in sheep and goats in other studies in China [ 38 , 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Among developing countries, a small number of C. parvum infections have been reported in goats and sheep from Asia, including China [ 17 , 47 , 48 ], India [ 49 ], Jordan [ 50 ] and Turkey [ 51 ]. Our results, however, are in contrast to those from studies conducted in most African countries including Egypt [ 37 ], Tunisia [ 52 ] and Ethiopia [ 53 ], where C. parvum has thus far not been reported in small ruminants. Cryptosporidium parvum was also absent in sheep and goats in other studies in China [ 38 , 41 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The present study also detected C. parvum in sheep and chickens. This is in contrast with many past studies which had demonstrated a rare occurrence of C. parvum in small ruminants and birds in Africa (Robertson et al 2020); with C. xiaoi predominating in sheep and goats in Ghana (Squire et al 2017) and C. ubiquitum predominating in lambs under 5 years in Ethiopia (Wegayehu et al 2017).…”
Section: Discussioncontrasting
confidence: 79%
“…In this investigation, G. duodenalis was detected in both black-boned sheep and goats, with respective prevalences of 21.8% (71/325) and 4.8% (16/336). The prevalence in black-boned sheep was higher than in other kinds of sheep previously reported in China (1.82–13.11%) [ 17 – 24 ], several parts of Australia (20.2%, 11.1%), Spain (11.1%, 19.2%), Ghana (12.9%), Italy (1.5%), Iran (19.8%) and Ethiopia (2.6%) [ 31 , 41 47 ], but lower than that in Switzerland (29.8%), Canada (38%), USA (25.4%), Belgium (35.8%), Norway (26.8%), some areas of Australia (63.7%), Spain (42%, 89.2%), Greece (37.3%) and Brazil (34%) [ 48 – 56 ]. As black-boned sheep age, the G. duodenalis prevalence tends to decrease, with a significant difference being observed among different age groups.…”
Section: Discussionmentioning
confidence: 87%